Budget management accountability analysis finance in the department of education Deli Serdang Regency - Sarmila, Sarmila; Lubis, Porkas Sojuangon; Suriana, Suriana (Indonesia Auditing Research Journal, 2024)
This study used qualitative research methods. The research method used is in-depth interviews on research subjects, observation and documentation. The purpose of this study is to describe how the Analysis of Financial Budget Management Accountability in the Education Office. The research subjects used in this study were selected using the purposive sampling method with the validity of the data using the triangulation technique. The location of this research is at the Office of the Education Office which is located at Jl. Work No. 1, Burning, District. Pagar Merbau, Deli Serdang Regency, North Sumatra 20517. In analyzing the data, the author uses a qualitative descriptive method of Accountability Analysis of Financial Budget Management in the Education Office, which is a technique with data analysis where the author first presents data from observations reported then the author analyzes accordingly. with the formulation of the problem and research objectives to be presented in the form of a scientific report. Based on the results of the research conducted, the SKPD Budget Realization Report presents information on the realization of revenues, expenditures, transfers, surplus /deficit and financing, each of which is compared to its budget in a certain period (PSAP no.2) . Budget Realization Report at the Deli Serdang district education office which has a very strategic meaning and urgency in the administration of the Education Office, where the report is substantially the realization of the implementation of programs/activities that are prepared and implemented taking into account the potential and socio-economic conditions of the region as one of the indicators for the progress and development of a region.